HTTP blocking in CN: instagram.com, twitter.com, whatsapp.com, youtube.com (China) - Voidly (2026)
WARNING severity censorship detected in China. Confidence: 85%. Data sourced from CensoredPlanet.
Censorship Incident ID: CN-2026-0006
Keywords: censorship; CN; censorship; warning